2011
DOI: 10.1002/bies.201000138
|View full text |Cite
|
Sign up to set email alerts
|

The changing faces of HP1: From heterochromatin formation and gene silencing to euchromatic gene expression

Abstract: Heterochromatin protein 1 (HP1) is a positive regulator of active transcription in euchromatin. HP1 was first identified in Drosophila melanogaster as a major component of heterochromatin. Most eukaryotes have at least three isoforms of HP1, which are conserved in overall structure but localize differentially to heterochromatin and euchromatin. Although initial studies revealed a key role for HP1 in heterochromatin formation and gene silencing, recent progress has shed light on additional roles for HP1 in proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
128
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(129 citation statements)
references
References 111 publications
1
128
0
Order By: Relevance
“…Beyond the evolutionary aspect, the context of cancer cells will be particularly interesting to consider given that frequent unbalance between HP1 paralogs is observed. 25 In addition, we should also consider the important role that HP1 proteins play in transcriptional regulation 12 and examine whether the different phenotypes observed herein could also be related, at least in part, to indirect transcriptional modulation of relevant DDR genes. Thus, transcriptome analysis under conditions of specific knockdown of the different HP1 paralogs would provide an entry point into this question that would then deserve a comprehensive study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the evolutionary aspect, the context of cancer cells will be particularly interesting to consider given that frequent unbalance between HP1 paralogs is observed. 25 In addition, we should also consider the important role that HP1 proteins play in transcriptional regulation 12 and examine whether the different phenotypes observed herein could also be related, at least in part, to indirect transcriptional modulation of relevant DDR genes. Thus, transcriptome analysis under conditions of specific knockdown of the different HP1 paralogs would provide an entry point into this question that would then deserve a comprehensive study.…”
Section: Methodsmentioning
confidence: 99%
“…Keywords: chromatin, DNA repair, epigenetics, HP1, homologous recombination, DNA end resection, non-histone chromatin proteins, DNA damage response and telomere stability. 11 Interestingly, even though mammalian HP1 paralogs and their orthologs in other metazoans share high levels of homology, 6 they can differ substantially in their properties and functions, 6,11,12 as illustrated with HP1γ that is mostly enriched in euchromatin. 13 Several recent reports have linked mammalian HP1 paralogs, as well as HP1 orthologs from flies and worms, to key steps of DNA damage signaling and DNA repair, thus suggesting an active role for these proteins in the DDR.…”
Section: Introductionmentioning
confidence: 99%
“…HP1 proteins are recruited to chromatin through H3K9 methylation (H3K9me) and/or direct interaction with additional chromatin associated factors (6). We therefore tested whether predicted H3K9 histone methyltransferases (HMTases) and potential interactors of HPL-2 also play a role in the ER stress response.…”
Section: Hpl-2 Acts In the Same Pathway As The Rb Homolog Lin-35 And Thementioning
confidence: 99%
“…However, very little is known on how specific chromatin proteins contribute to diverse stress responses in the context of a whole organism, or a specific tissue. Heterochromatin protein 1 (HP1) family proteins are conserved epigenetic regulators that control gene expression depending on the chromatin context (6). We have previously shown that the Caenorhabditis elegans HP1 homolog heterochromatin protein like-2 (HPL-2) plays a regulatory role in the dauer decision, an alternative developmental program that worms undergo under stressful conditions (7).…”
mentioning
confidence: 99%
“…Three mammalian HP1 isoforms, HP1a (CBX5), HP1b (CBX1), and HP1g (CBX3), have been identified in humans. Each of these heterochromatins contains two conserved domains, a chromodomain (CD) interacting with dimethylated Lys9 of histone H3 and a chromoshadow domain (CSD) interacting with the PxVxL motif of its partner, which are separated by a flexible hinge region (Kwon & Workman 2011). HP1 isoforms are known to exhibit different subnuclear localizations in interphasic nuclei.…”
Section: Introductionmentioning
confidence: 99%